STRATEGIC ISSUES REGARDING THE PRODUCT POLICY OF THE ROMANIAN MILITARY HIGHER EDUCATION INSTITUTIONS - STOENICĂ, Laurențiu (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
Educational services market competition requires military higher education institutions to adopt a marketing approach so that the dimension and containing of their educational offer to positively influence the demand for educational services. Understanding consumer needs and expectations of educational services, lead to the development of educational programs and specializations able to satisfy market needs manifested. The paper presents the analysis results on the range of educational services provided by the military higher education institutions from their strategic dimensions perspective, and positioning the military higher education institutions in Romanian higher education system